Effect of virulent and vaccine variants of influenza virus on the immunophenotype of dendritic cells generated from murine bone marrow - N. K. Akhmatova; A. A. Rtishchev; S. G. Markushin; A. M. Kostinova; E. A. Akhmatova; V. N. Stolpnikova; E. O. Kalinichenko; I. Zh. Shubina; I. A. Bisheva (Медицинская иммунология)
The aim of this study was to generate dendritic cells from the bone marrow of mice (DC) in vitro and to assess the effect of virulent and attenuated variants of influenza virus on the maturation of DCs. Granulocyte-macrophage colony stimulating factor (GM-CSF) and interleukin-4 (IL-4) were used in combination, to induce differentiation of mouse bone marrow (BM) mononucleocytes into DCs. On the 5th day, distinct variants of influenza virus were added to the cell culture, and the cells were additionally incubated for 2 days. The morphological characteristics of DCs, immunophenotype of DCs and expression of some Toll-like receptors were evaluated. On the 5th day of incubation. the DCs acquired typical morphological characteristics. DCs were large in size with an eccentrically located nucleous, often irregular in shape, with numerous processes. On the 7th day of incubation with influenza virus variants, their cytoplasm was somewhat denser. DCs acquired more processes, necessary for intercellular contacts. Expression levels of CD11c, a specific marker of BM-derived DCs, and of co-stimulatory molecules such as CD40, CD80, CD86, and MHC-II were elevated in mature DCs. Virulent versus attenuated strains of the influenza virus induced special variants of DCs differentiation, with respect to expression rates of differentiation markers, as well as expression of Toll-like receptors and costimulatory molecules. Conclusions. The in vitro cultured murine mononucleocytes derived from bone marrow can produce a large number of n-DCs, that can mature in the presence of different variants.During evolution of the DC immunophenotype treated with variant influenza viruses, we have found distinct signs of immunosuppression.The attenuated U-2 and M-26 influenza variants obtained by site-specific mutagenesis upon development of DCs immunophenotype, exhibited a decreased immunosuppressive activity and were not inferior to the cold-adapted (CA) reassortant for the most positions, but exceeded it in some instances. These studies can help to assess the criteria for evaluation the efficiency of in vitro developed influenza vaccines.